The comparative effects of 0.12% chlorhexidine and herbal oral rinse on dental plaque-induced gingivitis: A randomized clinical trial - Devaki Bhate; Sanjay Jain; Rahul Kale; Sangeeta Muglikar (Wolters Kluwer Medknow Publications, 2015)
Background: Chlorhexidine (CHX) is considered as a gold standard of antimicrobial rinses. Various herbal oral rinses are available in the market. However, little is known of its effectiveness. Aim: The aim of this study was to evaluate the clinical changes after the usage of herbal oral rinse and 0.12% CHX. Subjects and Methods: In a randomized clinical trial, 76 patients with dental plaque-induced gingivitis were assigned to Group I (Herbal Oral Rinse - Hiora; ) and 76 patients with dental plaque-induced gingivitis to Group II (0.12% Chlorhexidine-Peridex; ). Gingival index and Plaque index scores were recorded at baseline and 21 days after scaling. Results: Intragroup comparison in both groups showed that plaque index and gingival index scores were statistically significant after 21 days as compared to baseline. Intergroup comparison showed that plaque index scores and gingival index scores were statistically significant in Group II as compared to Group I. Conclusion: When herbal oral rinse was compared to 0.12% CHX, 0.12% CHX mouth rinse effectively reduced the clinical symptoms of plaque-induced gingivitis.